Determining the parties’ true choice of the seat of arbitration and lex arbitri - HWANG, Michael (Institutional Knowledge at Singapore Management University, 2010)
The selection of a seat of arbitration or the place of arbitration is sometimes not as straightforward as it seems. Because the seat of arbitration prima facie determines the law governing the conduct of the arbitration (also known as the “lex arbitri” or the “curial law”) thereby affecting the rights and liabilities of the parties, potential room for argument arises when that selection is not made with due care and precision. Three types (at least) of ambiguities may arise:(a) when there is ambiguity in the choice of the seat designated by the parties;(b) when the parties have designated a seat but have also chosen a lex arbitri different from that of the seat; and(c) when there is ambiguity in whether the domestic or the international arbitration regime within the designated seat should apply.The significance for counsel and clients is that the lex arbitri may turn out to be not what they had intended. The profound legal and practical implications attached to the seat of arbitration calls for practitioners to be aware of these pitfalls in designating a seat of arbitration. This article discusses the case law to illustrate different courts’ approach in resolving the three types of ambiguities outlined above.